2018
DOI: 10.3390/nano8121010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protonation, Hydroxylamination, and Hydrazination of g-C3N4 on the Performance of Matrimid®/g-C3N4 Membranes

Abstract: One of the challenges to continue improving polymeric membranes properties involves the development of novel chemically modified fillers, such as nitrogen-rich 2-D nanomaterials. Graphitic carbon nitride (g-C3N4) has attracted significant interest as a new class of these fillers. Protonation is known to afford it desirable functionalities to form unique architectures for various applications. In the work presented herein, doping of Matrimid® with protonated g-C3N4 to yield Matrimid®/g-C3N4 mixed matrix membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…However, the peak intensities corresponding to the heptazine rings are slightly reduced under light irradiation, indicating that the heptazine rings are involved in the photocatalytic reaction . Meanwhile, the peak at 3154 cm –1 can be assigned to the N–H bonds as shown in Figure S15b, confirming that HER reduction pathway processes occurred on heptazine rings of H@DBTD as evidenced by first-principles calculations, which have been discussed previously . Moreover, several new IR bands develop in the range of 1000–1300 cm –1 after photoirradiation as shown in Figure S15c.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…However, the peak intensities corresponding to the heptazine rings are slightly reduced under light irradiation, indicating that the heptazine rings are involved in the photocatalytic reaction . Meanwhile, the peak at 3154 cm –1 can be assigned to the N–H bonds as shown in Figure S15b, confirming that HER reduction pathway processes occurred on heptazine rings of H@DBTD as evidenced by first-principles calculations, which have been discussed previously . Moreover, several new IR bands develop in the range of 1000–1300 cm –1 after photoirradiation as shown in Figure S15c.…”
Section: Methodssupporting
confidence: 78%
“…64 Meanwhile, the peak at 3154 cm −1 can be assigned to the N−H bonds as shown in Figure S15b, confirming that HER reduction pathway processes occurred on heptazine rings of H@DBTD as evidenced by first-principles calculations, which have been discussed previously. 65 Moreover, several new IR bands develop in the range of 1000−1300 cm −1 after photoirradiation as shown in Figure S15c. The newly emerged IR peaks at 1072 and 1280 cm −1 can be attributed to the characteristic C−O stretching mode in C−OH and C−O−C, respectively.…”
Section: ■ Computational Methodsmentioning
confidence: 93%
“…This method involves the application of a g–C 3 N 4 –based layer to the membrane surface either by coating it or by grafting [ 49 ]. For designing g–C 3 N 4 –based hybrid membranes, several surface modification methods have been used, including self-assembly (using UV/plasma/chemical agents), vacuum filtration (using chemical agents), dip coating (using cross-linking), interfacial polymerization (using electrospinning), and grafting (using chemical agents) [ [50] , [51] , [52] ]. The most widely utilized technique is vacuum filtration because it is a quick way to make consistent g–C 3 N 4 –based composites on substrate materials.…”
Section: Introductionmentioning
confidence: 99%
“…Graphitic carbon nitride (g-C 3 N 4 ) nanosheets, hosting high-density molecular-sized pores composed of tri-s-triazine units in the entire 2D plane 14,15 , are considered ideal building blocks for molecular sieving membrane. Benefits to the nanometer-thin thickness and high-density nanopores, g-C 3 N 4 nanosheet membranes should be a superior candidate for H 2 separation 16,17 , which was already proved by theoretical investigations. For instance, Li et al 18 found that H 2 had the lowest diffusion barrier to go through the g-C 3 N 4 nanosheets by density functional theory (DFT) calculations, which resulted in a superior selectivity between H 2 and other larger gases.…”
mentioning
confidence: 88%